ANALISIS KINERJA KEUANGAN PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN SUMBAWA BARAT - ZULKIPLI, ZULKIPLI; ZULKIEFLIMANSYAH, ZULKIEFLIMANSYAH; YAMIN, YAMIN (Universitas Mahasaraswati K. Mataram, 2023)
Every regional government has an obligation to improve community services and welfare in a democratic, fair, equitable and sustainable manner. If the government is able to manage regional potential, both natural resource potential, human resources and financial resources optimally, then the government is considered capable of carrying out its obligations. The financial performance of the government and regions can be seen from the successful management of these potentials. The type of research used is quantitative research because the data is collected in the form of figures from regional financial reports. The data source that will be analyzed in this paper is secondary data. Secondary data is data obtained from the West Sumbawa Regency Public Works and Spatial Planning Service which relates to regional budgets and realization. Regional financial management must be implemented effectively and efficiently, transparently and accountably. Regional Revenue and Expenditure Budgets must also be transparently accountable to the public. Accountability is the final stage in regional financial management through reporting. The financial performance of the Public Works and Spatial Planning Department of West Sumbawa Regency from 2021-2022 is not good. This can be seen from the calculation results of the Effectiveness Ratio and Growth Ratio. The financial performance of the Regional Original Income (PAD) of the West Sumbawa Regency Public Works and Spatial Planning Service, when viewed from the Effectiveness Ratio, is categorized as ineffective, because the average effectiveness from 2021-2022 is below 60%, namely 21.38%. The details are as follows: In 2021 it will be 30.74%, and in 2022 it will be 12.02%